Celebrity Endorsement, TV Ads, and Purchase Intention: Mediating Role of Brand Image: Pengaruh Endorsement Selebriti dan Iklan Televisi terhadap Niat Pembelian: Peran Mediasi Citra Merek pada Iklan Produk Kecantikan - Brilyan Herman; Mudji Astuti (Academia Open, 2022)
This study employs a quantitative approach to examine the effect of celebrity endorsement and television advertising on purchase intention, with brand image serving as an intervening variable in the context of Wardah beauty product advertisements. Non-probability sampling was used, with accidental sampling yielding 100 respondents who were consumers of Wardah beauty products. Data analysis involved the use of the smart PLS 3.0 program to measure the inner and outer models. The findings indicate that celebrity endorsement and television advertising did not significantly affect purchase intention. However, both celebrity endorsement and television advertising had a significant impact on brand image. Furthermore, brand image did not have a direct influence on purchase intention, but it mediated the relationship between celebrity endorsement and purchase intention as well as between television advertising and purchase intention. These results contribute to a deeper understanding of the complex interplay between celebrity endorsement, television advertising, brand image, and purchase intention in the beauty product industry. Highlights: The impact of celebrity endorsement and television advertising: This study explores the influence of celebrity endorsement and television advertising on consumers' purchase intention in the context of Wardah beauty product advertisements. The mediating role of brand image: The research investigates the mediating role of brand image in the relationship between celebrity endorsement/television advertising and purchase intention, shedding light on the importance of brand perception in influencing consumer behavior. Implications for marketing strategies: The findings of this study have implications for marketing professionals in the beauty product industry, providing insights into the effectiveness of celebrity endorsement, television advertising, and brand image in shaping consumers' purchase intention. Keywords: Celebrity endorsement, television advertising, purchase intention, brand image, beauty product.